SYNTHESIS OF NANO - HYDROXYAPATITE AND NANO - FLUOROAPATITE PARTICLES BY SOL-GEL METHOD - Shoaib Khan; Madiha Pirvani; Sadaf Humayoun; Omair Anjum; Saima Akram; Muhammad Asif Nathani (ziauddin University, 2024)
Background: Hydroxyapatite is a material which resembles the composition and crystal structure of hard tissues in human body. It is being used in dentistry as a bioactive material in dental implants and is a major constituent in the bone regenerative materials. Fluoroapatite is also a bioactive material and is more stable than Hydroxyapatite. The fluoride content is anti - bacterial and is working very efficiently as a component of dental restorative materials. Objective: The objective is to synthesize the nano Hydroxyapatite and nanoFluoroapatite powder via sol-gel method, and compare the FTIR and Raman Spectrums of synthesized material with the FTIR and Raman of nano Hydroxyapatite and Fluoroapatite. Methods: The materials were synthesized by sol - gel method and then evaluated by the FTIR and Raman spectroscopy to confirm the chemical structure of both the materials. Results: FTIR and Raman Spectroscopy of the synthesized Hydroxyapatite and Fluoroapatite are then evaluated and compared with market grade materials, which confirm the presence of hydroxyl, phosphate and carbonate group in the obtained samples. Conclusion: Sol - gel is proved to be a reliable and simple method for the synthesis of nano Hydroxyapatite and Fluoroapatite particles. The obtained samples then compared with the available materials to confirm that the material synthesized is pure and chemically identical.